Transformational leadership and organizational performance: companies in Vietnam : Luận văn ThS. Kinh doanh: 603401 - Nguyen, Minh Hang (2019)
The study aims to investigate the relationship between transformational leadership and organizational performance, with the mediating roles of organizational learning and innovation. Data were collected from 86 respondents who are currently CEOs/ Directors/ Founder of the Vietnamese companies to analyze the model of the research. Based on the factor analysis, the 15 variables of the data collected were demonstrating the positive and significant influence that transformational leadership has on business performance, consequently gain some implications for practice in the Vietnamese context. Keywords: transformational leadership, organizational learning, innovation, organizational performance.